2002
DOI: 10.1152/ajpheart.01056.2001
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic preconditioning: triggering role of reactive oxygen and nitrogen species in isolated hearts

Abstract: We postulated that anesthetic preconditioning (APC) is triggered by reactive oxygen/ nitrogen species (ROS/RNS). We used the isolated guinea pig heart perfused with L-tyrosine, which reacts with ROS and RNS to form strong oxidants, principally peroxynitrite (ONOO Ϫ ), and then forms fluorescent dityrosine. ROS scavengers superoxide dismutase, catalase, and glutathione (SCG) and NO⅐ synthesis inhibitor N G -nitro-L-arginine methyl ester (L-NAME) were given 5 min before and after sevoflurane preconditioning stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…Our results also favor the importance of fasting in the modulation the enzymatic activity of the mitochondria and endoplasmic reticulum on drug metabolism because rats (high metabolic rate) did not ingest anything for more than one hour during the five days in which sevoflurane was administered (groups G2 and G4), which also favors induction of CYP2E1. Most studies have indicated a possible antioxidant effect of sevoflurane 15,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]35 ; however, depending on the tissue, this could be beneficial or harmful. For example, the cardiac protection induced by myocardial ischemic preconditioning is a benefic effect of ROS produced by sevoflurane 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also favor the importance of fasting in the modulation the enzymatic activity of the mitochondria and endoplasmic reticulum on drug metabolism because rats (high metabolic rate) did not ingest anything for more than one hour during the five days in which sevoflurane was administered (groups G2 and G4), which also favors induction of CYP2E1. Most studies have indicated a possible antioxidant effect of sevoflurane 15,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]35 ; however, depending on the tissue, this could be beneficial or harmful. For example, the cardiac protection induced by myocardial ischemic preconditioning is a benefic effect of ROS produced by sevoflurane 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that sevoflurane is capable of changing the flow of electrons along the respiratory chain, at the mitochondrial level, promoting the formation of ROS 14 . On the other hand, recent publications have discussed the phenomenon of anesthetic preconditioning, in which short exposure to sevoflurane is capable of protecting the myocardium and other organs against the deleterious tissue effects promoted by the process of ischemia/reperfusion 15,16 . Considering the extremely reduced number of studies on the antioxidant defense mechanism after multiple exposures to sevoflurane, the objective of the present study was to evaluate the activity of antioxidant enzymes of erythrocytes in Wistar rats treated with sevoflurane, with or without enzymatic induction of CYP2E1 with isoniazid.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of propofol-based TIVA, it is important to note that its oxygen free radical scavenging property may actually prevent other pre-conditioning effects [16,24]. Indeed, one of the triggers of anesthetic pre-conditioning is the formation of ROS species that can be inhibited by propofol.…”
Section: Clinical Translation Of Experimental Datamentioning
confidence: 99%
“…The generation of a small amount of ROS is essential in triggering myocardial protection induced by volatile anesthetics, while excessive oxidative stress and the production of large amounts of ROS are harmful [16]. Volatile anesthetics cause a small degree of subclinical harm (e.g., ROS generation) to trigger protective signaling against persistent and clinically harmful I-R injury, which can be viewed as pre-conditioning.…”
mentioning
confidence: 99%
“…Many potential mechanisms for this cardioprotection known as anesthetic preconditioning (APC) have been proposed [8]. Novalija et al demonstrated that APC by sevoflurane is initiated by reactive oxygen species (ROS) produced during sevoflurane exposure and reduces the burst formation of ROS after ischemia-reperfusion in isolated guinea pig hearts [9]. Recently, cardioprotection by sevoflurane has been shown to be mediated by ROS-induced 5' AMP-activated protein kinase (AMPK) activation which is a well known regulator of cellular energy status [10].…”
Section: Introductionmentioning
confidence: 99%